Gender analysis of the World Health Organization online learning program on Immunization Agenda 2030 - Nyasulu, Boetumelo Julianne; Heidari, Shirin; Manna, Michela; Bahl, Jhilmil; Goodman, Tracey (Frontiers in Global Women's Health, 2023)
The Immunization Agenda 2030 (IA2030), a global strategy to leave no one behind in immunization efforts and maximize the lifesaving efforts of vaccines, recognizes gender as an important cross-cutting dimension. To accelerate awareness about the IA2030 and to strengthen staff capacity, the World Health Organization offered an online learning program (WHO Scholar IA2030 Level 1 certification course) targeting those involved in country-level immunization planning to create action plans. An action plan in this context was a comprehensive document created by course participants outlining strategic priorities, identifying an immunization challenge, and prioritizing recommendations, best practices, and innovative implementation strategies for enhancing their national immunization program and global collaboration efforts. The action plans that were submitted in the 2021 course were analyzed to assess the extent to which participants were successful in mainstreaming gender into their action plans. A sample of action plans (111 out of 256) with a peer review score above 75% was selected to carry out a narrative thematic analysis to examine the incorporation of gender and categorize the identified barriers and approaches to those barriers. The analytical categories used for the narrative analysis were based on the gender-related barriers to immunization outlined in the IA2030 Gender Guide. It was evident that many of the well-documented barriers in the IA2030 Gender Guide were indeed incorporated by course participants, and they offered various approaches and ideas to address these barriers that are also supported in other studies. The action plans of the course participants reflected that limited access to quality services, lack of control over resources, and unequal power differentials further impact health-seeking behavior and outcomes. This analysis showcased that this online program had a positive impact in raising awareness of the need to identify and address gender-related barriers to immunization and mainstream gender in immunization activities.